Analisis Perilaku Organisasi terhadap kinerja Karyawan di D'Besto di Lubuk Begalung - Muhammad Rasyid Ridha; Rika Savitri; Puja Rima Yenti; Zulma Hendra; Vivi Nila Sari (BADAN PENERBIT STIEPARI PRESS, 2024)
d'Besto is a fast food restaurant designed for Indonesian families who crave the culinary experience of delicious fried chicken and burgers., d'Besto offers a partnership package with an investment value of IDR 200 million. However, the investment value can change depending on the location and area of ​​the partner's outlet. With this capital, it is projected that the daily turnover will reach Rp. 5-Rp. 15 million, while the net profit will be 25 percent. So it requires a structure or. Organizational behavior is the study of how individuals and groups act within an organization. This includes an understanding of interpersonal dynamics, group processes, organizational structure, culture, and the work environment. The main goal of this study is to increase organizational effectiveness by understanding, predicting, and managing human behavior in an organizational context.. This PBL aims to analyze the influence of organizational behavior on employee performance. D Besto The method used is a quantitative approach with observation and interviews Organizational behavior includes several aspects such as leadership, communication, motivation, and a conducive work environment that has a significant impact on employee performance. The PBL results on D Besto show that positive and supportive organizational behavior can increase productivity, efficiency and high employee performance.